RELATIONS BETWEEN OBESITY INDICATORS AND AEROBIC CAPACITY OF PUPILS - Mateja Kunješić; Marko Badrić; Ivan Prskalo (Sport Scientific And Practical Aspects, 2025)
The aim of research was to determine the association between of obesity indicators and aerobic capacity of primary school pupils. The study included 333 pupils (178 boys and 155 girls) aged 7-11 years from two primary schools in Zagreb. To determine the association between functional capacity and body composition, four variables of anthropometry and one variable for assessing functional abilities were used. A statistically significant association between aerobic capacity and indicators of obesity was determined by Pearson's correlation coefficient at a significance level of p <0.05. Results indicate a significant negative correlation between functional abilities and body mass index (BMI) in boys (-, 18) and girls (-, 23). The results of correlation between body fat percentage (% BF) and functional capacity (FC) indicate a statistically significant association in boys (-, 25) and girls (-, 38). In the upper arm volume a statistically significant negative correlation with functional abilities in boys is proven (-, 16), while the results in girls show a negative correlation but not statistically significant. Also, the results show that in girls there is no statistically significant relationship between functional abilities and upper arm volume while in boys relationship is statistically significant (-, 16). Based on the obtained results it can be concluded that increased body fat percentage (BF%) has effect on physical performance. Increased body mass index (BMI) reduces the results of functional abilities in boys and girls. Volume of the body is negatively correlated with aerobic capacity. The level of aerobic capacity increases by reducing the fat content. It also reduces chances of various diseases appearance and improves overall physical fitness of primary school pupils.